On stability of equilibrium in linear thermoviscoelasticity (Archives of Mechanics - Test, 2006)
We present some results concerning the uniform Lyapunov stability of the generalized solution of an equilibrium problem for thermoviscoelastic materials [9]. These results are similar to those obtained in [4-7]. The results in [4] were subsequently developed for exterior domains in [8].